Instability in Geophysical Flows - Smyth, William D. (Physical Sciences, 2019)
An Open Access overview of physical processes that generate instability in geophysical systems. It covers classical analytical approaches together with numerical methods for quick prediction of stability in a system. Including exercises and MATLAB® coding examples, it can be used for self-study or advanced courses in the environmental sciences.